Saccharides in atmospheric PM2.5 in tropical forest region of southwest China: Insights into impacts of biomass burning on organic carbon aerosols. (December 2022) - Wang, Xin; Chen, Yukun; Guo, Xiao; Dai, Wenting; Liu, Yali; Wu, Feng; Li, Jianjun
Abstract: Biomass burning (BB) in South and Southeast Asia has a strong impact on regional air quality, yet its impact on atmospheric PM2.5 of tropical rainforest regions, a background region occupying a large area in South Asia, has rarely been investigated. In this work, we performed one-year PM2.5 sampling during December 2018 to October 2019 at a tropical rainforest site in southwest China. PM2.5 mass concentration, major chemical components, and ten saccharides were determined to study seasonal variations of PM2.5 chemical composition, and further to understand possible impacts of BB to organic carbon (OC) aerosols at this background region. The concentration levels of PM2.5, major PM2.5 components, and total saccharides were significantly higher in dry season than in wet season. Besides, PM2.5, OC, and total saccharides were highly correlated (R 2  > 0.64, p  < 0.001) during the sampling period, suggesting they might share common sources. Source apportionment of saccharides revealed that BB was the main source in both seasons. Furthermore, the contributions of BB to OC (BB/OC) were estimated using levoglucosan as a molecular tracer while levoglucosan's chemical degradation was considered. It was found that over 80% of LG was degraded in both seasons, suggesting BB sources were largely from the transport of external air mass. The estimated BB/OC were over 50%, indicating BB was an important source of OC and likely of PM2.5 in both seasons. The air-mass backward trajectory analysis and active fire spots data indicate intense BB emission sources were from South and Southeast Asia in dry season and the BB emissions in southern region of China could impact on the studied area in wet season. Graphical abstract: Image 1 Highlights: Distinct seasonal variations of concentrations of atmospheric PM2.5, major PM2.5 components, and saccharides. Biomass burning (BB) was a major source of organic carbon aerosols in both dry and wet seasons. BB was mostly from South and Southeast Asia in dry season and the impact of BB in wet season was from southern China.